Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Pegawai UKPBJ Kabupaten Kepulauan Mentawai - Yani, Putra; Isfarudi, Isfarudi; Koeswara, Hendri (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2024)
This study aims to analyze the influence of competency level, workload, incentives, and motivation on the performance of employees in the Procurement Services Unit (UKPBJ) of the Mentawai Islands Regency Government. This research employs a quantitative approach with a survey method. Data were collected through questionnaires distributed to UKPBJ employees as respondents. Data analysis was conducted using multiple linear regression to examine the influence of independent variables (competency, workload, incentives, and motivation) on the dependent variable (employee performance).The results show that competency level has a positive and significant effect on employee performance. Workload has a negative and significant effect, indicating that excessive workload can reduce employee performance. Incentives were found to have a positive and significant effect, implying that adequate incentives can enhance employee performance. Motivation also has a positive and significant effect on performance, suggesting that highly motivated employees tend to work more optimally. Simultaneously, these four variables significantly influence the performance of UKPBJ employees. These findings suggest that the Mentawai Islands Regency Government should prioritize competency training, implement balanced workload distribution policies, and design comprehensive incentive programs to foster employee motivation and enhance overall performance